KAJIAN FILOSOFIS “KSAYAN IKANG PAPA NAHAN PRAYOJANA” DAN IMPLEMENTASINYA DALAM ETIKA KEPEMIMPINAN PEMERINTAHAN (PERSEPEKTIF KEARIFAN LOKAL) - Diah Puspita Ernawati; I Gusti Ngurah Suwetha (Jurnal Ilmiah Wahana Bhakti Praja, 2018)
The basic values of philosophy in an area that is almost forgotten, at the present time seems to be still relevant to be used to support the task, especially in governance, which is conducted by Government Leaders. Nowadays, The Government Leaders often get the attention from their own public regarding their government implementation.  Apparently this issue needs an innovation and new strategy in implementing government programs, given the present political demands have been increasingly bold and very aggressive in appreciating the policy pursued by the government. Meanwhile, the Government leaders are still monotonous in implementing their policy.In implementing that public demand, the government leaders need to understand the culture and tradition as local wisdom or local genius applies in their territory so that it is easy to integrate the policies made and desired by the government can be combined with local customs, culture and traditions, so in running the government and implementing government in the specific region can be implemented in accordance with the wishes and will of the local community.Bali is very famous with its local culture, which is based on the traditional philosophical values they embrace. Government leaders in managing the government should always collaborate between government programs with their customs, traditions and local culture, which in their daily terms are called empowering local wisdom based on the philosophy of "Tri Hita Karana" in providing public services for the realization of prosperity for their people.  A leader's job as contained in the Epic Ramayana, "Papa Ikang Kesayan Nahan Prayojana" which means; the tasks of a leader are realizing prosperity, peace and tranquility for his people.Keywords: Government Leaders; Community Prosperity; Local wisdom